1996
DOI: 10.1111/j.1447-0756.1996.tb00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Phospholipid Antibodies in Preeclampsia and Their Binding Ability for Placental Villous Lipid Fractions

Abstract: The results suggest that one cause of preeclampsia is the production of antiphospholipid antibodies that bind to placental villous membrane antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…In preeclampsia, many autoantibodies such as anti nuclear, anti phospholipid, anti endothelial antibody, anti angiotensin receptor agonistic antibody and others were reported 16,17 . Zhou et al 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In preeclampsia, many autoantibodies such as anti nuclear, anti phospholipid, anti endothelial antibody, anti angiotensin receptor agonistic antibody and others were reported 16,17 . Zhou et al 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A procoagulant contribution from activated blood platelets may be less important, considering that a significantly lower number of PS-expressing, plateletderived microvesicles are found in pre-eclampsia, relative to that found during normal pregnancy [176]. In some but not all cases, patients with pre-eclampsia are positive for antibodies directed against lipid-bound b 2 -glycoprotein I [177][178][179]. Both conditions have been proposed to contribute to thrombosis in the intervillous spaces on the maternal side of the placenta, impeding placental perfusion.…”
Section: Pre-eclampsiamentioning
confidence: 94%
“…In other words, the relationship between hypertension, cerebral hemorrhage and infarction is complex. Furthermore, studies have suggested immune system involvement in pregnancy hypertension [38][39][40][41], but not in essential hypertension.…”
Section: Pih Susceptibility Genesmentioning
confidence: 99%